Late‐stage magma flow in a shallow felsic reservoir: Merging the anisotropy of magnetic susceptibility record with numerical simulations in La Gloria Pluton, central Chile. Issue 5 (16th May 2013) - Gutiérrez, F.; Payacán, I.; Gelman, S. E.; Bachmann, O.; Parada, M. A.
Abstract : [1] La Gloria Pluton is a 10 Myr old epizonal intrusion located in the southern Andes. We present anisotropy of magnetic susceptibility data that indicate a magnetic fabric that is mainly oblate. We find that lineations are weak and have a N‐NW trend with a nearly horizontal dip, while foliations are more pronounced, have NW trends, and have dips that vary from vertical at the walls of the intrusion to horizontal at the center and under the roof of the chamber. To interpret these magmatic fabrics, we developed a time‐dependent 2‐D magmatic fluid dynamic numerical simulation. Our model is calibrated with MELTS and accounts for the coupled processes of cooling, crystallization, and degassing of a magma chamber. Simulations indicate that the resulting convective flow pattern in the crystallizing reservoir is consistent with the magnetic fabric, which is largely produced in the shear zone between the convecting liquid‐dominated core and the growing solidification fronts adjacent to the walls. The magnetic fabric records the last increment of strain induced by convective magmatic flow in the cooling reservoir during crystallization at the rheological magma locking point along solidification fronts. Despite the small size of the pluton, the core of the chamber remains thermally insulated from the colder host rocks, surviving up to 20 kyr above the solidus, which allows enough time for the extraction of residual leucogranitic melt and partial late magmatic reactive recrystallization. The results of the simulations are also consistent with the previously determined compositional and mineralogical zonation patterns in the pluton. Key Points: Magnetic fabrics in La Gloria Pluton vary in a simple fashion The simulated convective flow pattern insulates magma reservoirs Magnetic fabric records the last increment of strain of convection